Application of Unsupervised Multivariate Analysis Methods to Raman Spectroscopic Assessment of Human Dental Enamel - Otel, Iulian (2022)
This work has been financially supported by Fundação para a Ciência e a Tecnolo-gia through the LIBPhys funding UID/FIS/ 04559/2021 Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.